Sintering Behavior of Magnesium-Substituted Fluorapatite Powders Prepared by Hydrothermal Method - S. Nasr; K. Bouzouita (Bioinorganic Chemistry and Applications)
Magnesium-substituted fluorapatite powders were synthesized by hydrothermal method, and their sintering behavior was investigated by dilatometry in the temperature range 25–1100°C. Analysis of the obtained powders by X-ray diffraction and 31P NMR spectroscopy showed that the powders consisted of a single apatite phase and no amorphous phase has been formed. Compared to pure fluorapatite, the shrinkage of the substituted samples occurred in two steps and the temperature at which the sintering rate was maximum is lower. In addition, the shrinkage was interrupted by an expansion of the samples due to the formation of a liquid phase. The latter phase led to the crystallization of needle-crystals by a dissolution-diffusion-reprecipitation process.